Noninvasive Imaging of Endogenous Neural Stem Cell MobilizationIn VivoUsing Positron Emission Tomography - Maria Adele Rueger; Heiko Backes; Maureen Walberer; Bernd Neumaier; Roland T. Ullrich; Marie‐Lune Simard; Beata Emig; Gereon R. Fink; Mathias Hoehn; Rudolf Graf; Michael Schroeter (2010)
Neural stem cells reside in two major niches in the adult brain [i.e., the subventricular zone (SVZ) and the dentate gyrus of the hippocampus]. Insults to the brain such as cerebral ischemia result in a physiological mobilization of endogenous neural stem cells. Since recent studies showed that pharmacological stimulation can be used to expand the endogenous neural stem cell niche, hope has been raised to enhance the brain's own regenerative capacity. For the evaluation of such novel therapeutic approaches, longitudinal and intraindividual monitoring of the endogenous neural stem cell niche would be required. However, to date no conclusive imaging technique has been established. We used positron emission tomography (PET) and the radiotracer 3′-deoxy-3′-[ 18 F]fluoro- l -thymidine ([ 18 F]FLT) that enables imaging and measuring of proliferation to noninvasively detect endogenous neural stem cells in the normal and diseased adult rat brain in vivo . This method indeed visualized neural stem cell niches in the living rat brain, identified as increased [ 18 F]FLT-binding in the SVZ and the hippocampus. Focal cerebral ischemia and subsequent damage of the blood–brain barrier did not interfere with the capability of [ 18 F]FLT-PET to visualize neural stem cell mobilization. Moreover, [ 18 F]FLT-PET allowed for an in vivo quantification of increased neural stem cell mobilization caused by pharmacological stimulation or by focal cerebral ischemia. The data suggest that noninvasive longitudinal monitoring and quantification of endogenous neural stem cell activation in the brain is feasible and that [ 18 F]FLT-PET could be used to monitor the effects of drugs aimed at expanding the neural stem cell niche.